Fuzziness Measure, Quantified Sematic Mapping and Interpolative Method of Approximate Reasoning in Medical Expert Systems. - Hồ, Nguyễn Cát; Sơn, Trần Thái; Khang, Trần Đình; Việt, Lê Xuân (Journal of Computer Science and Cybernetics, 2012)
-